2014
DOI: 10.1145/2513567
|View full text |Cite
|
Sign up to set email alerts
|

Charging and Storage Infrastructure Design for Electric Vehicles

Abstract: Ushered by recent developments in various areas of science and technology, modern energy systems are going to be an inevitable part of our societies. Smart grids are one of these modern systems that have attracted many research activities in recent years. Before utilizing the next generation of smart grids, we should have a comprehensive understanding of the interdependent energy networks and processes. Nextgeneration energy systems networks cannot be effectively designed, analyzed, and controlled in isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Although they used a lifecycle cost analysis approach to comparing different storage systems, the operational costs of fast chargers were not discussed. Momtazpour, et al [20] demonstrated a systematic data-mining method that can be used to identify locations for placing charging and storage infrastructure; but they did not consider some important measures such as battery life, energy storage, and economic performance. In summary, most studies do not integrate the battery storage system into the EV charging infrastructure's design and construction process.…”
Section: Battery Storage Technologymentioning
confidence: 99%
“…Although they used a lifecycle cost analysis approach to comparing different storage systems, the operational costs of fast chargers were not discussed. Momtazpour, et al [20] demonstrated a systematic data-mining method that can be used to identify locations for placing charging and storage infrastructure; but they did not consider some important measures such as battery life, energy storage, and economic performance. In summary, most studies do not integrate the battery storage system into the EV charging infrastructure's design and construction process.…”
Section: Battery Storage Technologymentioning
confidence: 99%
“…One typical approach is to apply clustering techniques to point recharging http://dx.doi.org/10.1016/j.trc.2015.08.018 0968-090X/Ó 2015 Elsevier Ltd. All rights reserved. demands and then deploy stations to the cluster centers (e.g., Ip et al, 2010;Momtazpour et al, 2014). The flow-capturing approach aims at locating charging stations to maximize the amount of traffic flow that travels along a path with at least one station (Hodgson, 1990;Berman et al, 1992Berman et al, , 1995Hodgson and Berman, 1997;Shukla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Definition of spatial criteria for EV charging station (CS) placement, based on infrastructure, city features, urban planning, and EV user profiles [18,25,[30][31][32][33][34][35][36][37].  Geometric, mathematical, and statistical modeling-such as multicriteria analysis and clustering, geographic information system (GIS), databanks [30,32,35,[38][39][40][41][42], and social networks [43].  Studies on the demand for electric charging, batteries, and the impact of charging stations on electric grids [19,29,32,39,41,42,[44][45][46].…”
mentioning
confidence: 99%
“… Geometric, mathematical, and statistical modeling-such as multicriteria analysis and clustering, geographic information system (GIS), databanks [30,32,35,[38][39][40][41][42], and social networks [43].  Studies on the demand for electric charging, batteries, and the impact of charging stations on electric grids [19,29,32,39,41,42,[44][45][46].  Several authors make prescriptions for EV charge-point rating, optimizing their allocation.…”
mentioning
confidence: 99%
See 1 more Smart Citation